RIM101-Dependent and -Independent Pathways Govern pH Responses in Candida albicans - Davis, Dana (American Society for Microbiology, 2000)
Growth and differentiation of Candida albicans over a broad pH range underlie its ability to infect an array of tissues in susceptible hosts. We identified C. albicans RIM101, RIM20, and RIM8 based on their homology to components of the one known fungal pH response pathway. PCR product-disruption mutations in each gene cause defects in three responses to alkaline pH: filamentation, induction of PRA1 and PHR1, and repression of PHR2. We find that RIM101 itself is an alkaline-induced gene that also depends on Rim20p and Rim8p for induction. Two observations indicate that a novel pH response pathway also exists. First, PHR2 becomes an alkaline-induced gene in the absence of Rim101p, Rim20p, or Rim8p. Second, we created strains in which Rim101p activity is independent of Rim20p and Rim8p; in these strains, filamentation remains pH dependent. Thus, pH governs gene expression and cellular differentiation in C. albicans through both RIM101-dependent and RIM101-independent pathways.